Remedial Teaching Patterns in Improving Islamic Religious Education Learning Outcomes for Junior High School Students - Ratnayanti Ratnayanti; Hasbi Hasbi; St. Marwiyah (Journal of Indonesian Islamic Studies, 2021)
This study aims to: 1) determine the pattern of remedial teaching in Islamic Religious Education subjects at UPT SMP Negeri 4 Masamba, North Luwu Regency 2). Get an overview of the implementation of remedial teaching to improve student learning outcomes in Islamic Religious Education subjects at UPT SMP Negeri 4 Masamba, North Luwu Regency, 3) Knowing the results of remedial teaching in Islamic Religious Education subjects at UPT SMP Negeri 4 Masamba, North Luwu Regency. This research is qualitative research that uses a pedagogical, and sociological, didactic-methodical approach. The subjects of this study consisted of the Principal 2) Teachers 3) Coaches, and Students at SMP Negeri 4 Luwu Utara. Data analysis in qualitative research generally starts from data collection, data reduction, presentation of data, and concluding. The results of the research and analysis conclude as follows: 1) The pattern that is often used by Islamic Religious Education teachers in remedial teaching is adjusted to the existing subject matter but what is often used is the technological and international pattern with a withdrawal model, 2) The implementation of remedial teaching in The UPT of SMP Negeri 4 Luwu Utara is carried out in the form of a. Giving re-learning with different methods and media, b. Providing specific guidance, for example, individual guidance, c. Giving specific training tasks, d. Utilization of peer tutors, 3) The results of remedial teaching at UPT SMP Negeri 4 Luwu are carried out well, this can be seen in the achievement of students' scores who are successful in getting the minimum criteria scores after participating in remedial teaching.